Crystal Structure of the Lactose Operon Repressor and Its Complexes with DNA and Inducer - Lewis, Mitchell; Chang, Geoffrey; Horton, Nancy C.; Kercher, Michele A.; Pace, Helen C.; Schumacher, Maria A.; Brennan, Richard G.; Lu, Ponzy (Science (American Association for the Advancement of Science), 1996)
The lac operon of Escherichia coli is the paradigm for gene regulation. Its key component is the lac repressor, a product of the lacI gene. The three-dimensional structures of the intact lac repressor, the lac repressor bound to the gratuitous inducer isopropyl-β-D-1-thiogalactoside (IPTG) and the lac repressor complexed with a 21-base pair symmetric operator DNA have been determined. These three structures show the conformation of the molecule in both the induced and repressed states and provide a framework for understanding a wealth of biochemical and genetic information. The DNA sequence of the lac operon has three lac repressor recognition sites in a stretch of 500 base pairs. The crystallographic structure of the complex with DNA suggests that the tetrameric repressor functions synergistically with catabolite gene activator protein (CAP) and participates in the quaternary formation of repression loops in which one tetrameric repressor interacts simultaneously with two sites on the genomic DNA.